Impact of Environmental Education on Tertiary Level Students’ Knowledge, Attitude and Perception (Teacher’s World: Journal of Education and Research, 2023)
This research discussed the status of environmental knowledge, attitude and perceptions of university students and the relationship between environmental knowledge and attitudes among them. A mixed-method design was adopted to examine tertiary level students’ environmental knowledge and attitudes by employing a pre-test and a post-test conducted before and after an Environmental Education (EE) course. Those tests consisted of 15 multiple choice questions and 18 attitude measuring items rated on a five-point Likert scale. For supporting the quantitative data, a Focus Group Discussion (FGD) was also conducted for the purpose of exploring students’ perceptions on EE. A total of 88 students (72 for tests and 16 for FGD) participated in this study. The findings showed a significant improvement of the students in terms of knowledge and favorable environmental attitudes. The participants also expressed a positive perception of the EE course. Finding ways of implementing EE for students of all levels can be the next subject for further research.Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.54-66